Co-Occurrence of Symptoms and Gut Microbiota Composition Before Neoadjuvant Chemotherapy and Radiation Therapy for Rectal Cancer: A Proof of Concept. Issue 3 (July 2021) - González-Mercado, Velda J.; Lim, Jean; Yu, Gary; Penedo, Frank; Pedro, Elsa; Bernabe, Raul; Tirado-Gómez, Maribel; Aouizerat, Bradley
Purpose: To examine a) whether there are significant differences in gut microbial diversity and in the abundance of gut microbial taxa; and b) differences in predicted functional pathways of the gut microbiome between those participants with high co-occurring symptoms and those with low co-occurring symptoms, prior to neoadjuvant chemotherapy and radiation therapy (CRT) for rectal cancer. Methods: Rectal cancer patients (n = 41) provided stool samples for 16 S rRNA gene sequencing and symptom ratings for fatigue, sleep disturbance, and depressive symptoms prior to CRT. Descriptive statistics were computed for symptoms. Gut microbiome data were analyzed using QIIME2, LEfSe, and the R statistical package. Results: Participants with high co-occurring symptoms (n = 19) had significantly higher bacterial abundances of Ezakiella, Clostridium sensu stricto, Porphyromonas, Barnesiella, Coriobacteriales Incertae Sedis, Synergistiaceae, Echerichia-Shigella, and Turicibacter compared to those with low co-occurring symptoms before CRT (n = 22). Biosynthesis pathways for lipopolysaccharide, L-tryptophan, and colanic acid building blocks were enriched in participants with high co-occurring symptoms. Participants with low co-occurring symptoms showed enriched abundances of Enterococcus and Lachnospiraceae, as well as pathways for β-D-glucoronosides, hexuronide/hexuronate, and nicotinate degradation, methanogenesis, and L-lysine biosynthesis. Conclusion: A number of bacterial taxa and predicted functional pathways were differentially abundant in patients with high co-occurring symptoms compared to those with low co-occurring symptoms before CRT for rectal cancer. Detailed examination of bacterial taxa and pathways mediating co-occurring symptoms is warranted.